Peculiarities of near-electrode relaxation processes in the polyethylene melt filled with graphite and carbon black - Kuryptya, Ya.A.; Savchenko, B.M.; Kovalchuk, O.V.; Kovalchuk, T.M.; Shostak, T.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
By using the oscilloscope method within the frequency range 10 to 10⁶ Hz at the temperature 492.1 K and pressure 11.31 MPa at the output of the single-screw extruder, the dielectric properties of the composite melt – linear low-density polyethylene + 20 wt.% of graphite + 10 wt.% of carbon black – have been investigated. It has been shown that in the whole frequency range, near-electrode processes significantly effect on charge transfer. For the frequencies less than 100 Hz, in the near-electrode area the conductance is provided with hopping movement of electrons. For the frequencies over 100 Hz, charge transfer occurs through the ion movement. It has been shown that the transfer of ions in the near-electrode area can be described using the relaxation process that, unlike the vast majority of processes described in the publications, meets the wellknown relations only in terms of the complex conductivity. It has been shown that, in the terms of the complex conductivity, this relaxation process can be approximated with Debye equation, as well as it has been estimated the relaxation time (8.5 ms) for this process. According to the parameters included in the Debye equation, it has been estimated the thickness of the near-electrode area (17 μm) and shown that it practically coincides with the sizes of graphite particles.